RANCANG BANGUN GAME KETANGKASAN MEMBUAT BURGER BERBASIS ANDROID (Information Technology and Telematics, 2014)
Abstract - Game is one of a very large industry. Basically the game is created just for a means of entertainment only but it would be better if the game was created as a learning tool. Learning can also train agility in thought and action. Learning a strategy or a plan to resolve a problem. Here the authors try to apply a game to learn and play. The game is about how to make a burger with a predetermined order. Making game using the Corona SDK and Lua programming language. The end result of the development of this system in the form of an arcade game application that presents a game that is not only fun and entertaining, but also challenges. Train players to complete missions that require dexterity of movement, speed of thought and ingenuity in seeing objects in the game to complete the missions also given to train your memory.   Keywords: Game, Corona, Lua, Agility.